A first report of biodeterioration caused by cyanobacterial biofilms of exposed fossil bones: A case study of the middle Pleistocene site of La Polledrara di Cecanibbio (Rome, Italy). (January 2016) - Marano, Federica; Di Rita, Federico; Palombo, Maria Rita; Ellwood, Neil Thomas William; Bruno, Laura
Abstract: La Polledrara di Cecanibbio is a Pleistocene fossiliferous deposit near Rome (Italy) where large quantities of bones, belonging mainly to elephants, have been discovered and 'musealized' under an enclosing structure. The prevailing environmental conditions inside the museum and the exposition in situ of the fossilized remains have resulted in the development of phototrophic biofilms on the bones and the nearby sediments. Samples of bones and sediment were investigated with different microscopy techniques (light, confocal laser scanning, scanning electron and petrographic microscopes) that allowed the identification of the cyanobacterium Leptolyngbya sp. as the almost entirely dominant organism of the biofilms. The present study identifies for the first time endolithic activity of this cyanobacterium on exposed fossilized bones. There was some indication that this species was euendolithic but this remains to be elucidated. The development of these phototrophic biofilms greatly reduces the aesthetic value of the site and evidence suggests that they may cause extensive structural damage to the bones, threatening the scientific and cultural assets of one of the richest fossiliferous deposits in Italy. This study on the biodeterioration of fossil remains gives useful insights for the conservation of this spectacular site. Highlights: Biodeterioration in a Pleistocenic fossiliferous deposit was investigated. Investigation was carried out with different microscopy techniques. Leptolyngbya sp. has been identified as the main biofilm-forming microorganism. Endolithic activity has been demonstrated on fossil bones.